Mathematical and computational methods of non-Newtonian, multiphase flows - Sawko, Robert (Cranfield University, 2012)
The research presented in this thesis is concerned with the development of numerical techniques and mathematical models for non-Newtonian uids and two-phase ows in pipes and channels. Single phase, turbulent ow calculations of non-Newtonian uids were performed initially. Based on the literature a revised approach to wall modelling is proposed and implemented. The approach uses analytical and experimental analyses of the turbulent boundary layer structure. A comparison with the standard approach is presented. The interaction between turbulence and non-Newtonian behaviour is studied by examining the rate of strain induced by uctuating components of velocity. The statistical analysis of published DNS data is performed. Finally, a model is proposed where the turbulent rate of strain is determined from turbulence quantities used by the Reynolds-averaged Navier{Stokes model and used in the calculation of molecular viscosity. For two-phase ow, the solution procedure using periodic boundary conditions was developed under an assumption of a at interface. The numerical technique was veri ed by comparing to an analytical result obtained for laminar ow in a channel. An extension to three dimensional ow is performed. With periodic boundary conditions standard turbulence models are applied to two-phase strati ed ow. Several models and their corrections for twophase ow are assessed and a new model is proposed. The numerical studies were carried out primiarily in the open-source code OpenFOAM, but initial attempts were made in commercial packages such as STAR-CD and FLUENT. Experimental data collected from the literature are used to verify the results showing good agreement in pressure drops and phase fractions.